Kolumbijske mirovne skupnosti in rekonstrukcija državljanstva na vojnem območju - Sanford, Victoria (Časopis za kritiko znanosti, 2005)
In Columbia, following several years of maginal life on the urban peripheries after being displaced from their villages by paramilitary violence, some 12,000 Columbian peasants negotiated the return to their land (in the middle of the war zone) as Peace Communities in 1999. These Peace Communities have sought to rebuild community life as neutrual, unarmed civilians. Moreover, they sought to build interdependent utopian communities based on citizen participation, mutual respect and collective survival. Given the large numbers of displaced people living in desparate circumstances of misery, how and why have these communities sought not only reconstruction, but also a better, more peaceble way of life in the mids of war? While living in war is not unique, efforts to build utopian communities in war zones represent highly creative response by seemingly powerless peasants to the violence that crashes unbidden upon them. In an era of lawlessness, they reassert their right as citizens. This article explores how this reconstitution of citizenship represents a new kind of political power grounded in community integrity and moral courage. This power is not a violent nature, but rather power derived from the moral imagination - power that creates new realities by pushing the frontiers of the possible in the midst of the war zone.
Keywords: citizenship; Kolumbija; peace; razseljenost; Latin America; državljanstvo; mir; social movements; peasants; družbena gibanja; mirovne skupnosti; kmetje; Latinska Amerika; displacement